2015
DOI: 10.1016/j.bmc.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mer kinase inhibitors by virtual screening using Structural Protein–Ligand Interaction Fingerprints

Abstract: Mer is a receptor tyrosine kinase implicated in acute lymphoblastic leukemia (ALL), the most common malignancy in children. The currently available data provide a rationale for development of Mer kinase inhibitors as cancer therapeutics that can target both cell autologous and immune-modulatory anti-tumor effects. We have previously reported several series of potent Mer inhibitors and the objective of the current report is to identify a chemically dissimilar back-up series that might circumvent potential, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…They also submitted to virtual screening 156 known TAM inhibitors (from public databases) docking most of them into the DFG-in model and only five into the DFG-out, finding that a terminal p-fluorophenyl group is crucial for type II inhibitors [10,107]. Very recently, the pyrazolopyrimidine TAM inhibitor UNC569 [107] has also been used as a reference compound in a virtual screening study aimed at finding Mer kinase inhibitors [108], owing to its high resolution crystal structure in complex with the Mer kinase domain [107]. Of note, UNC569 was found to be effective against lymphoblastic leukemia in vitro and in vivo [109].…”
Section: Development Of Axl Inhibitors 41 From Chemistry To Pharmacmentioning
confidence: 99%
“…They also submitted to virtual screening 156 known TAM inhibitors (from public databases) docking most of them into the DFG-in model and only five into the DFG-out, finding that a terminal p-fluorophenyl group is crucial for type II inhibitors [10,107]. Very recently, the pyrazolopyrimidine TAM inhibitor UNC569 [107] has also been used as a reference compound in a virtual screening study aimed at finding Mer kinase inhibitors [108], owing to its high resolution crystal structure in complex with the Mer kinase domain [107]. Of note, UNC569 was found to be effective against lymphoblastic leukemia in vitro and in vivo [109].…”
Section: Development Of Axl Inhibitors 41 From Chemistry To Pharmacmentioning
confidence: 99%
“…Only four compounds of the 3200 screened have shown activity above a threshold of 30 % resulting in a hit rate of 0.12 % (4 hits/3200 tested). Therefore, our VS approach has demonstrated an $200-fold (24 %/0.12 %) improvement over a random screen [10]. This study also exemplifies that screening of commercial catalogs can yield tractable hits appropriate as starting points for the hit-to-lead progression.…”
Section: Introductionmentioning
confidence: 55%
“…Therefore, all possible means must be deployed to improve the odds of getting a sizable number of confirmed actives out of very small sets of virtual hits. We have recently demonstrated that a post-docking score based on structural protein-ligand interaction fingerprints (SPLIF) can greatly improve VS success rates [10,11]. The SPLIF-based score exploits the idea that a compound that can mimic "native" ligand-protein interactions (e.g., enzyme-substrate interactions) is more likely to be a true hit than a random compound with a decent docking score.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein–inhibitor interaction fingerprints are high-level presentations of these complexes, where the binding mode of a small molecule inhibitor is encoded in a series of physical interactions. The exact composition of such a fingerprint can vary significantly from simple binary representations that inform about the presence or absence of a particular interaction, to quantitative measurement of the strength of interactions between protein and ligand atoms. , Protein–ligand interaction fingerprints have been used extensively to characterize virtual screening results to identify small molecules that share a common mode of interaction with known binders . Fingerprinting has been used to characterize conserved binding modes across families of potential drug targets such as human kinases and G protein-coupled receptors. , One major advantage of fingerprinting is the ability to simultaneously evaluate a large number of protein–ligand complexes, which can identify signature interactions to guide SBDD.…”
Section: Integrative Computational Methods To Evaluate Inhibitor Pote...mentioning
confidence: 99%